Substantia nigra hyperechogenicity in essential tremor and Parkinson's disease: a longitudinal study. (27th June 2019) - Cardaioli, G.; Ripandelli, F.; Paolini Paoletti, F.; Nigro, P.; Simoni, S.; Brahimi, E.; Romoli, M.; Filidei, M.; Eusebi, P.; Calabresi, P.; Tambasco, N.
Abstract : Background and purpose: Essential tremor (ET) and Parkinson's disease (PD) sometimes overlap in their clinical expression with ET preceding PD onset, often leading to misdiagnosis. Transcranial sonography (TCS) has been shown to be a valid and non‐invasive diagnostic tool to identify early idiopathic PD and to differentiate it from ET. The purpose of this study was to investigate the relevance of substantia nigra hyperechogenicity in patients with ET. Methods: A total of 138 patients (79 with PD, 59 with ET) and 50 matched controls underwent TCS examination at baseline. All patients were followed in a 3‐year longitudinal assessment. Results: A total of 10 subjects were excluded from the analysis due to the bilateral absence of a temporal acoustic window. During the follow‐up period, 11 of the patients with ET developed new‐onset parkinsonian features, without fulfilling criteria for PD diagnosis (ET+). Nine patients developed clinical features meeting diagnostic criteria for probable PD (ET‐PD). Patients with ET− did not develop parkinsonian features. For each group, the maximum size of the substantia nigra hyperechogenicity was as follows: 5.62 ± 5.40 mm 2 in the control group, 19.02 ± 14.27 mm 2 in patients with PD, 9.15 ± 11.26 mm 2 in patients with ET−, 20.05 ± 13.78 mm 2 in patients with ET+ and 20.13 ± 13.51 mm 2 in patients with ET‐PD. ET‐PD maximum values were significantly different from controls. Maximum values in patients with ET+ were different from both controls and patients with ET−. Conclusion: Substantia nigra hyperechogenicity in ET seems to represent a risk marker for developing early parkinsonian symptoms or signs in the 3 years following TCS assessment.